On Properties of Root Elements in the Problem on Small Motions of Viscous Relaxing Fluid - Zakora, D. (Журнал математической физики, анализа, геометрии, 2017)
In the present work, the properties of root elements of the problem on small motions of a viscous relaxing fluid completely filling a bounded domain are studied. A multiple p-basis property of special system of elements is proven for the case where the system is in weightlessness. The solution of the evolution problem is expanded with respect to the corresponding system.